Leitura e escrita literária como resistência à adversidade. - Campos, Elani Cristina da Silva (Universidade Federal do Tocantins, 2023)
This work discusses and analyzes how reading and literary writing imply different modes of resistance and psychic (re)configuration of three characters in A menina que roubava livros, by Markus Zusak (2007); A menina que não sabia ler, by John Harding (2010) and O diário de Anne Frank, by Anne Frank (2019). It aims to present the importance of the different processes of reading and writing for the lives of adolescents, with their subjective implications, mainly in situations of adversity. This is qualitative bibliographic research, associated with an interpretative analysis, theoretically supported by Annie Rouxel, Gèrard Langlade, Neide Luzia Rezende (2013), Roger Chartier (1990), Michelè Petit (2013, 2010, 2008) and Antonio Candido (2006, 2004, 1989), who discuss the power of literature, reading and writing, considering the contexts full of obstacles that the characters experience. As a method of interpretive analysis, fragments of the works were selected to constitute the research corpus, being used to highlight, and prove the aspects and modes of resistance and psychic (re)configurations of the characters. The data collected and analyzed were fundamental to confirm the power that literature exerts in the construction of a type of subjectivity (support), which points to the survival of subjects in different contexts of ills and pain. Therefore, in this study, reading and writing symbolize psychic transformation, also providing a driving force to fight for life and endure the adversities of the world.